2017
DOI: 10.1002/lary.27045
|View full text |Cite
|
Sign up to set email alerts
|

Brain volume changes in hyposmic patients before and after olfactory training

Abstract: 3b. Laryngoscope, 128:1531-1536, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 46 publications
(115 reference statements)
3
67
3
1
Order By: Relevance
“…It is important to point out that the improvements in olfactory ability with training did not reflect changes in the OBs for either patient group . Our nonsignificant changes to OB volumes are at odds with studies showing increases in olfactory patients undergoing medical treatment, spontaneous recovery, and studies in healthy subjects .…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…It is important to point out that the improvements in olfactory ability with training did not reflect changes in the OBs for either patient group . Our nonsignificant changes to OB volumes are at odds with studies showing increases in olfactory patients undergoing medical treatment, spontaneous recovery, and studies in healthy subjects .…”
Section: Discussioncontrasting
confidence: 57%
“…in the OBs for either patient group. 30,34 Our nonsignificant changes to OB volumes are at odds with studies showing increases in olfactory patients undergoing medical treatment, 29,31 spontaneous recovery, 57 and studies in healthy subjects. 58 The current findings seem to suggest that improvements induced through training in olfactoryimpaired individuals may be, at least in part, a top-down effect through plasticity of the central nervous system and increased attention.…”
Section: Training Effects On Obmentioning
confidence: 77%
See 2 more Smart Citations
“…MCID was defined as a .5.5 or .6 increase in TDI scores by the individual study authors. In 2006, Gudziol et al 33 demonstrated that an increase of 5.5 points in TDI composite scores corresponded to more than 60% of patients reporting subjective olfactory improvement; 4 studies use this value as 18 Prospective cohort study 39 COT 8 mo Gellrich et al (2018) 26 Prospective case-control study 61 COT 3 mo Hummel et al (2009) 16 Prospective cohort study 24 COT 3 mo Hummel et al (2017) 27 Retrospective cohort study 170 COT 3 mo Kollndorfer et al (2015) 17 Prospective cohort study 10 COT alone vs COT and vitamin A 3 mo Konstantinidis et al (2013) 28 Prospective cohort study 81 COT 4 mo Konstantinidis et al (2016) 19 Prospective cohort study 111 Short-term COT vs long-term COT 4 mo, 14 mo Oleszkiewicz et al (2018) 29 Prospective 20 Prospective cohort study 125 Combination 1 OT vs combination 2 OT 6 mo Saatci et al (2020) 31 Prospective cohort study 60 Olfactory training ball vs COT 3 mo…”
Section: Study Characteristicsmentioning
confidence: 99%